Interfac 2025 UiTM cawangan Selangor: ignites passion and unity across the campus - Ab Rahman, Ateeqa Irdiena Sofea; Jahidin, Aisyah Hasyila (Faculty of Pharmacy, 2026)
The courts came alive once again as students battled it out for glory at the Inter-Faculty Sports Championship (INTERFAC) 2025.Organised by Sports Unit of Student Affairs Department (HEP), UiTM Selangor Branch (UCS), Puncak Alam Campus, the competition was successfully executed by the Society of Pharmacy Students (SOPHYS) 2024/2025together with the Faculty of Pharmacy Student Secretariat (SMF) 2024/2025 as the organising committee. Held on 6 - 7 and 13 - 14 December 2025, the events brought together students from all faculties in a vibrant celebration of athleticism, teamwork, and campus spirit.